High-Throughput Sequencing to Investigate Associations Between HLA Genes and Metamizole-Induced Agranulocytosis - Cismaru, Anca Liliana; Grimm, Livia; Rudin, Deborah; Ibañez, Luisa; Liakoni, Evangelia; Bonadies, Nicolas; Kreutz, Reinhold; Hallberg, Pär; Wadelius, Mia; , EuDAC Collaborators; Haschke, Manuel; Largiadèr, Carlo R.; et al. (Frontiers in Genetics, 2020)
Background and objective: Agranulocytosis is a rare and potentially life-threatening complication of metamizole (dipyrone) intake that is characterized by a loss of circulating neutrophil granulocytes. While the mechanism underlying this adverse drug reaction is not well understood, involvement of the immune system has been suggested. In addition, associations between genetic variants in the Human Leukocyte Antigen (HLA) region and agranulocytosis induced by other drugs have been reported. The aim of the present study was to assess whether genetic variants in classical HLA genes are associated with the susceptibility to metamizole-induced agranulocytosis (MIA) in a European population by targeted resequencing of eight HLA genes. Design: A case-control cohort of Swiss patients with a history of neutropenia or agranulocytosis associated with metamizole exposure (n=53), metamizole-tolerant (n=39) and unexposed controls (n=161) was recruited for this study. A high-throughput resequencing (HTS) and high-resolution typing method was used to sequence and analyze eight HLA loci in a discovery subset of this cohort (n=31 cases, n=38 controls). Identified candidate alleles were investigated in the full Swiss cohort as well as in two independent cohorts from Germany and Spain using HLA imputation from genome-wide SNP array data. In addition, variant calling based on HTS data was performed in the discovery subset for the class I genes HLA-A, -B, and -C using the HLA-specific mapper hla-mapper. Results: Eight candidate alleles (p < 0.05) were identified in the discovery subset, of which HLA-C*04:01 was associated with MIA in the full Swiss cohort (p < 0.01) restricted to agranulocytosis (ANC < 0.5x109/L) cases. However, no candidate allele showed a consistent association in the Swiss, German and Spanish cohorts. Analysis of individual sequence variants in class I genes produced consistent results with HLA typing but did not reveal additional small nucleotide variants associated with MIA. Conclusions: Our results do not support an HLA-restricted T cell-mediated immune mechanism for MIA. However, we established an efficient high-resolution (three-field) eight-locus HTS HLA resequencing method to interrogate the HLA region and demonstrated the feasibility of its application to pharmacogenetic studies.